Evaluation of the Benelux Innovativeness in the Years 2003-2011 - Kobryń , Andrzej; Prystrom, Joanna (Studia Oeconomica Posnaniensia, 2018)
Due to the importance of innovation in boosting the socio-economic development of individual countries, this article presents an assessment of the innovation level in the Benelux countries (Belgium, the Netherlands and Luxembourg), which are considered to be some of the most innovative and best developed countries in the world. The level of innovation is affected by various factors, which influence the innovation of individual economies and thus far has not yet been thoroughly investigated. For this reason, using a quantitative - TOPSIS method - it was taken up to try to rank the Benelux countries' economies in terms of the level of innovation, in the light of chosen determinants of innovative capacity. The analysis showed that the highest level of innovativeness characterizes the economy of Luxembourg, followed by the economy of the Netherlands and Belgium. It was also found that the indicators of innovativeness for Luxembourg and the Netherlands generally decrease, while in the case of Belgium is shown to be slow but stable with a growing trend.